Clinical effect of the proximity of epidural blood patch injection to the leakage site in spontaneous intracranial hypotension. (2nd November 2018) - Lee, Jin Young; Lee, Mi Ji; Park, Hue Jung; Park, Jin Hyoung; Jeong, Hee Joon; Oh, Min Seok; Son, Yong Hun; Sim, Woo Seog
Abstract: Background: Epidural blood patch (EBP) has been shown to be an effective treatment option for spontaneous intracranial hypotension (SIH). We investigated whether response to the EBP was related to the distance of the injection site from the leakage site in patients with SIH. Methods: We reviewed patients with SIH who underwent EBP at a single hospital. Patients were assigned to group R (response after EBP) or group N (no response after EBP). We then analyzed the demographics, clinical characteristics, leakage site, leakage length, EBP injection level and distance from leakage site, and injected EBP volume. Results: Sixty-two patients were included in the analysis. The overall response rate to EBP was 59.7% (37 patients). The leakage length and injection distance from the leakage site did not differ between the two groups. Age, gender, body mass index, leakage site, and EBP volume did not differ significantly between the two groups. Conclusion: The clinical effect of EBP in SIH was not affected by leakage length or injection distance to leakage site. Further large studies must be conducted to investigate the efficacy of targeted EBP for SIH.